Swarm - Westerfeld, Scott; Lanagan, Margo, 1960-; Biancotti, Deborah, 1971- (Westerfeld, Scott. Zeroes., 2016)
As they celebrate the opening of their underground nightclub, the Zeroes, six teenagers with unique abilities, learn about the sinister power of Swarm, who uses a crowd's rage to kill--and who loves killing Zeroes.